(untitled) (Vietnam Journal of Community Medicine, 2025)
Introduction: Patient safety is a top priority in clinical practice, especially for newly graduated nurses who are at high risk of making errors due to a lack of experience. Kiken Yochi Training (KYT) has been proven effective in risk identification and reducing medical errors. However, the application of KYT in nurse training remains limited in Vietnam. Objective: This study aims to evaluate the effectiveness of KYT in enhancing risk identification skills and preventing medical errors among newly graduated nurses. Methods: A quasi-experimental intervention study was conducted on 86 newly graduated nurses undergoing clinical training at Cho Ray Hospital from 2024 to 2025. The intervention group participated in KYT training sessions, which included theoretical instruction and practical exercises based on risk identification models. The effectiveness of the program was assessed before and after the intervention using a risk identification skills test and a survey on nurses’ perceptions of KYT training. Results: After the intervention, the percentage of nurses accurately identifying risks increased from 54.7% to 83.2% (p < 0.05). The mean scores for recognizing potential risks and preventing medical incidents significantly improved. KYT contributed to changing the incident reporting culture, helping to create a safer working environment. Additionally, 92.4% of nurses rated KYT as useful in clinical practice and reported feeling more confident in patient care. Discussion: KYT enables newly graduated nurses to recognize potential risks in clinical settings, thereby proactively preventing medical errors. The findings align with international studies, reinforcing the effectiveness of KYT in nurse training. Conclusion: KYT is an effective method to enhance risk identification skills and medical error prevention for newly graduated nurses. Expanding KYT training in nursing education could contribute to improving patient safety in hospitals.